EFFECT OF NaOH AND Ca(OH)₂ ALKALI TREATMENT TIME ON PURUN TIKUS FIBER PROPERTIES - Akhmad Syarief; Valentino Krisna Mukti; Iphan Radam; Muhammad Nizar Ramadhan; Akhmad Ghifary Budianto; Fadlyannur Fadlyannur; Aulia Aufa Ramadasari; Rizqi Ilmal Yaqin (Scientific Journal of Mechanical Engineering Kinematika, 2026)
Purun tikus fiber (Eleocharis dulcis) is a promising natural fiber for environmentally friendly composite reinforcement due to its abundant availability and relatively high cellulose content. However, the presence of lignin, hemicellulose, and surface impurities can reduce interfacial bonding and mechanical performance. This study investigated the effect of alkali treatment type and immersion time on the mechanical and morphological properties of single purun tikus fibers. The fibers were treated in 5 wt.% NaOH and Ca(OH)₂ solutions for 3, 6, and 9 h, with three specimens prepared for each treatment variation. Mechanical characterization included single-fiber tensile testing based on ASTM C1557 to determine tensile strength, strain, and elastic modulus, pull-out testing to evaluate interfacial shear strength, and field emission scanning electron microscopy (FESEM) analysis to observe surface morphology changes. The results showed that the the most favorable treatment condition was obtained using NaOH for 3 h. Under this condition, the interfacial shear strength increased from 2.858 MPa to 3.394 MPa, corresponding to an improvement of approximately 18.8%, while the tensile strength was maintained at 0.681 MPa, close to that of the untreated fiber (0.685 MPa). In contrast, longer immersion times of 6 and 9 h reduced the tensile strength and interfacial performance, indicating fiber degradation due to excessive alkalization. FESEM observations confirmed that short-duration alkali treatment improved surface cleanliness and roughness, whereas prolonged treatment caused cracks and structural damage. These findings indicate that controlled NaOH treatment is more effective than Ca(OH)₂ in improving the suitability of purun tikus fiber as a composite reinforcement.